Water-filled technique for therapeutic pancreato-biliary EUS in patients with surgically altered anatomy - Mangiavillano, Benedetto; Carrara, Silvia; Eusebi, Leonardo H.; Auriemma, Franceasco; Bianchetti, Mario; Repici, Alessandro (Endoscopy International Open, 2021)
One of the main challenges encountered by endosonographers is performing diagnostic and interventional pancreato-biliary endoscopic ultrasound (EUS) procedures in the presence of surgically altered upper gastrointestinal anatomy. We describe the water-filled technique (WFT) for EUS examination and treatment of the pancreato-biliary region in patients with surgically altered upper gastrointestinal anatomy. Using the WFT, the scope is advanced up to the gastro-jejunal anastomosis and, after placing the tip of the scope 2 cm beyond it, enlargement of the jejunal lumen is obtained by water instillation of the jejunal loop. An enlargement of more than 1.5 cm allows advancement of the tip of the scope under EUSguidance up to the duodenum, in a retrograde way. The WFT is useful for reaching the ampullary area and performing diagnostic and therapeutic EUS in patients with surgically altered anatomy. The technique is also reproducible and can be easily used by endoscopists who regularly perform EUS.